Skin Temperature in Young Women with Low Values of Adipose Tissue - Vitaliy Epishev; Anna Nenasheva; Yulia Korableva; Alexander Belenkov; Alina Episheva; Seyed Morteza Tayebi (The Society of Aging and Physical Activity (SAPA), 2019)
Background. Skin temperature is an important indicator of the functional status of the body. Infrared thermal images of the body surface or its separate parts could be the indicator of body composition and, probably, the criterion of the functional activity of muscles. Objectives. This study aims to find a correlation between the average values of skin temperature in different parts of the body and the components of body composition in young women with low values of adipose tissue (FAT % = 20.73±5.50; BMI = 20.23±2.44). Methods. The study involved 69 healthy women aged 18-20 (BMI = 20.23±2.44). Participants were subjected to a 15-minute temperature adaptation in the room with a temperature of 22-24°С and humidity of 45-50%. We measured body composition using bioelectrical impedance analysis and taking eight photos of different body areas with the help of the thermal infrared camera. Results. Correlation analysis allowed us to reveal temperature correlations with BMI and FAT%. The most significant values were registered between FAT% and tmean (r=-0.36), FAT% and tshinBL (r=-0.39), FAT% and tshin BR (r=-0.38). Conclusion. To forecast FAT% for this sample, the skin temperature of the shin is the most informative parameter (decrease by 1% results in the increase in FAT% by 1-1.5%). Moreover, we made a hypothesis that the differences between tmean of shins and hips indicate the postural balance: tshinmean ˃ t hipmean is responsible for the shin strategy; tshinmean ˂ thipmean indicates the hip strategy.